A STUDY ON THE NON PERFORMING ASSETS OF BANKS IN INDIA - Kesavan, Varun (International Journal For Research In Business, Management And Accounting, 2016)
Among all functions, primary function of banks is to lend funds as loans to various sectors such as agriculture, industry, personal loans, housing loans etc., however in recent times the banks have become very cautions in extending loans. The reason of such an initiative is the problem pertaining to non-performing assets (NPAs). An asset becomes nonperforming when it ceases to generate income for the bank. Prior to 31st March, 2004 a nonperforming asset was defined as a credit facility in respect of which the interest or instalment of principal has remained past due for a specified period of time which was four quarters. Due to the improvements in payment and settlement system, recovery climate, up gradation of technology in the banking system etc., it has been decided to dispense with past due concept. This paper is going to study on the NPAs of banks in India with highest Npa’s and also highlighting the causes, factors affecting NPA’s based on conceptual background.